Application of Physical Factors in the Chronic Endometritis Treatment: a Review - Olga O. Borisevich; Anatoliy D. Fesyun; Natalya V. Kotenko (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. Chronic inflammation in the uterine cavity is a fairly common problem in women of reproductive age, which negatively affects the state of the reproductive potential of the population. AIM. To present a scientific review of domestic and foreign literature covering modern methods and approaches of physical medicine used in the rehabilitation treatment of women with chronic endometritis. CONCLUSION. After analyzing the studied sources, we can conclude that the use of restorative medicine factors significantly expands the possibilities of treating chronic endometritis. Due to the use of complex or monotherapeutic techniques based on natural and preformed physical factors, it is possible to achieve outstanding results in restoring the morphofunctional potential of the endometrium. The main obstacle to the introduction of physical medicine approaches in practical healthcare is their low background, insufficient number of randomized studies that allows to use these methods as part of clinical recommendations. Further search and study of suitable non-drug regimens for chronic inflammation in the uterine cavity is needed, which will reduce the need for drug therapy.